Nilai-Nilai Kearifan Lokal dalam Tari Gagak Mandiq dan Relevansinya terhadap Kehidupan Sosial Masyarakat Lenek Daya Lombok Timur - Nurul Hikmah; Syahrul Amar; Suhupawati Suhupawati; Lalu Wahyu Andi Purnama (Universitas Hamzanwadi, 2025)
Traditional dance is a cultural archive that preserves the knowledge, values, and life orientation of its supporting community. This study examines the history of the Gagak Mandiq Dance, identifies local wisdom represented through its performance elements, and analyzes its relevance to the social life of the Lenek Daya community in East Lombok. A qualitative field-research design was employed. Data were collected through observation, in-depth interviews with nine informants representing the village government, art studio management, performers, community leaders, residents, and youth, as well as documentation. Data analysis involved reduction, display, and conclusion drawing, while source and technique triangulation were used to strengthen credibility. The findings show that Amaq Raya created the Gagak Mandiq Dance in 1956 after observing a crow bathing. The movements of ngindang, nyengkeng, bowing, flapping, trembling, and cleansing the body form a symbolic system that communicates balance between humans and nature, ecological awareness, humility, patience, courage, physical and spiritual purity, togetherness, mutual cooperation or besiru, and proper conduct. These values remain relevant because they are connected to the practices of besiru and begibung, character education for younger generations, religiosity, communal identity, and village social activities. Preservation through the Teruna Bebadosan Art Studio, village-government support, education, digital documentation, and adaptive performance packaging is therefore necessary. Adaptation should improve accessibility and attractiveness without separating the dance from the meanings, memories, and social practices through which the Lenek Daya community recognizes it as a living cultural identity.